Treatment of visceral artery aneurysms and pseudoaneurysms with the use of cerebral flow diverting stents: initial experience - Rabuffi, Paolo (CVIR Endovasc, 2020)
BACKGROUND: Flow-diverter stents (FDS) are designed to maintain laminar flow in the parent artery and sidebranches and to promote thrombosis of the aneurysm. Although these devices were developed for use in intracranial circulation, FDS could be employed to treat aneurysms regardless of their location, when anatomic factors may limit the efficacy of classic endovascular techniques. The objective of this study is to describe the initial experience of a single center in the treatment of visceral artery aneurysms and pseudoaneurysms (VAA-VAP) with cerebral FDS, analyzing safety, efficacy and 1-year outcome. Between 2016 and 2018 six patients (4 women, mean age 57.6) underwent treatment with FDS of 4 VAA and 2 VAP located in renal (4), hepatic (1) and splenic arteries (1). Mean aneurysm diameter was 14.3 mm (range 8–22). All the aneurysms had sidebranches arising from the neck or had an unfavorable dome-to-neck ratio. Technical success, safety, efficacy and 1-year outcome were analyzed. Follow-ups (FU) with Color-Doppler US and CTA ranged from 12 to 36 (mean 20) months. RESULTS: Technical success was achieved in all cases. There were no aneurysm rupture nor reperfusion after exclusion. Five out of six (83.3%) FDS were patent at each FU; all the aneurysms showed shrinkage with a mean dimensional reduction rate of 55.8%. Sac thrombosis was observed in 4 aneurysms at 1 (n = 3) and at 12-month FUs. There was one sidebranch occlusion with evidence of a small area of kidney hypoperfusion at the 12-month FU, which was asymptomatic. In one patient, a reintervention was needed because CTA showed a severe in-stent stenosis, which was symptomatic. Mean hospitalization was 4.1 days. CONCLUSIONS: Treatment of morphologically complex VAA and VAP with cerebral FDS proved to be safe and efficient. Stronger evidence from larger populations are required.